The Influence of Human Resource Professionalism, Village Asset Management, Asset Utilization Optimization, and the Role of BUMDes Human Resources on Increasing Village-Generated Revenue (PADes) - Tri Sumiyanti; Taswan; Anisa Kusumawardani; Muhammad Farras Alfitra; Jati Widya Iswara; Abdul Fajar (CV Edujavare Publishing, 2026)
The Influence of Human Resource Professionalism, Village Asset Management, Asset Utilization Optimization, and the Role of BUMDes Human Resources on Increasing Village-Generated Revenue (PADes)